The Effect of Implementation of Accrual-Based Government Accounting Standards on The Quality of Financial Statements Regional Government - Azwar Rivai Nasution (International Journal of Applied Finance and Business Studies, 2020)
The aim of this research is to examine the effect of the application of government accounting standard accrual to quality of financial statement local government in the department of empowerment communities and village government at South Tapanuli Government. The population of this research are employees in the department of empowerment communities and village government. The total number of samples of this research are 35 people, which their data collection are taken using questionnaires. This research is tested using by simple regression. Research shows that the application of government accounting accrual standard has a positive and significant effect on the quality of local government financial statements